Versatility of the facial artery myomucosal island flap in neopharyngeal reconstruction. Issue 2 (5th October 2016) - Frisch, Thomas
ABSTRACT: Background: The facial artery myomucosal (FAMM) island flap is a cheek flap, pedicled on the facial artery and suitable for small to medium‐sized reconstructions of the oral cavity and neighboring areas. A novel transposition of the flap to the hypopharynx after laryngectomy is presented in this report. Methods: A 58‐year‐old man, previously irradiated, was laryngopharyngectomized because of a new supraglottic carcinoma. An unexpected need for a flap was solved by tunneling a FAMM island flap lateral to the mandible. The reach and size of the flap were sufficient to close the defect. Results: Vitality of the flap was ascertained by fiber endoscopy. No donor‐site morbidity was seen. Postoperatively, the patient had a minor stomal fistula with spontaneous healing. Conclusion: The pedicled FAMM island flap may be considered for smaller reconstructions of the upper hypopharynx. Accessibility, low donor‐site morbidity, and recipient tissue similarity count among the advantages. © 2016 Wiley Periodicals, Inc. Head Neck 39: E29–E33, 2017